A HISTORICAL LOOK AT THE MODERN PRINCIPLES AND PRACTICE OF REAL ESTATE OF DEVELOPMENT - Гиесов Ильхом Каримович; Рузибоев Сулаймон Баходирович (American Journals, 2023)
The review of the article presents the chronological history of modern development. This serves as a background against which the development of models for estimating the real value of development can be traced.
Keywords: Development, institutional, urban planning process, modern development.